Quasi-experimental study on the effectiveness of a house officer preparatory course for medical graduates on self-perceived confidence and readiness: a study protocol - Abdul Rashid, Aneesa; Shariff Ghazali, Sazlina; Mohamad, Iliana; Mawardi, Maliza; Roslan, Dalila; Musa, Husna (BMJ Publishing Group, 2019)
Introduction Being a house officer (HO) is said to be associated with high levels of stress, leading to mental health problems and sometimes to quitting the medical profession altogether. In Malaysia, the number of HOs completing training on time is slowly declining, with increasing annual dropout rates. Feeling incompetent is one of the contributors towards this growing problem. This study aimed to evaluate the effectiveness of a 3-day pre-HO intervention module in addressing participants’ confidence, readiness and psychological well-being in preparation for their HO training.Methods and analysisThe pre-HO intervention is the ‘Medicorp’ module that includes clerkship, experience sharing, hands-on skills training, common clinical cases and introduction of the local healthcare system. This is a pre-post quasi-experimental study lasting 1 year, with three assessment time points—at pretraining, immediately after training and 1 month into the participants’ HO-ship. The study is currently ongoing and involves 208 participants who attended the course in Malaysia. Participants with known psychiatric illness, working HOs and medical students are excluded. A pretested, self-administered questionnaire that includes baseline sociodemography, adaptation of the International Medical University (IMU) Student Competency Survey and the Depression Anxiety Stress Scale has been adopted, and 1 month follow-up will be conducted by telephone. Data will be analysed using SPSS V.24. The primary outcome is change in confidence level, while the secondary outcomes are changes in the readiness and psychological well-being of the participants.Ethics and disseminationThis study protocol has received ethics approval from Ethics Committee for Research Involving Human Subjects Universiti Putra Malaysia and the National Medical Research Registry Malaysia. Written informed consent has been obtained from each participant. Results will be disseminated through journals and conferences, especially those involved in medical education specifically looking into the training of medical doctors.